Dylematy tożsamości. Wokół autowizerunku filozofa w powojennej myśli francuskiej - Kwiek, Marek (Wydawnictwo Naukowe IF UAM, 1999)
The present book is devoted to the changing (social and political) self-image of the philosopher in French culture from Georges Bataille and Alexandre Kojève to the late Michel Foucault and recent debates about postmodernity. My point of departure is to analyze a general passage from the French Hegel to the French Nietzsche in the sixties from the perspective of the questions of social and political role, place, tasks and obligations of the philosopher in culture. I am drawing a sketch in which a general change of a „master thinker” results in a change in the philosopher’s self-image: from a „community-oriented” to a „text-oriented” (or from a „Hegelian” to a Nietzschean”)one. The self-image of the philosopher who wants to revolutionize the social world with the immediate help of his/her philosophy (analyzed on the basis of Kojève) is shown to be gradually being replaced with the self-image of the philosopher who wants to get rid of social burden he used to carry and social mission he used to be engaged in and to produce philosophical texts (analyzed on the basis of French Nietzscheans: Deleuze and Klossowski). I am discussing different formulations of this basic opposition: from Jean-Paul Sartre („the aesthete”/”the engaged writer”) to its reversal in Roland Barthes („authors”/writers”) to its criticism in Georges Bataille and Maurice Blanchot to Michel Foucault’s attempt to go beyond the very oppositions pertaining to „writing” as such in his dichotomy of „universal intellectuals”/”specific intellectuals”. I am also redescribing the French „Heidegger affair” and the American- French „Paul de Man affair” from the perspective of the two opposing self-images of the philosopher in culture: a communitarian and textual one, as well as I am presenting and criticizing an attempt to go beyond this very opposition in Michel Foucault’s „aesthetics of existence”. The present book is devoted to relations between philosophy and politics, between history and knowing, writings and revolutions, thought and action, changing and interpreting the world – seen from the point of view of the figure of the philosopher; at the same time the modernity/postmodernity debate is redescribed in terms of differing self-images philosophers feel obliged to impose on themselves. Pertaining to French culture, the book asks subsequent, carefully selected philosophers questions that are equally well valid elsewhere e.g. in America or in Poland of the times of transformation and the choice of French thinkers for its analyses is determined by the French shadow of great intellectual debates from the „Dreyfus affair” to recent „silence of the intellectuals” debate that falls on the figure of the “philosopher” today.
Keywords: intelektualiści; autowizerunek filozofa; powojenna filozofia francuska; zaangażowanie polityczne; tożsamość intelektualisty; Jean-Paul Sartre; Georges Bataille; Martin Heidegger; sprawa Heideggera; Paul de Man; sprawa Paula de Mana; Michel Foucault; postmodernizm; ponowoczesność; etyka ponowoczesna; Alexandre Kojeve; Fenomenologia ducha; G.W.F. Hegel; francuski Hegel; Fryderyk Nietzsche; nietzscheanizm; nietzscheanizm francuski; tekstualizm; literatura a filozofia; Roland Blanchot; Pierre Klossowski; troska o siebie; ontologia teraźniejszości; Roland Barthes; l'engagement; polityka i filozofia; filozofia polityki; filozofia a nazizm; zaangażowanie społeczne; intelektualiści francuscy; wspólnotowość; estetyka egzystencji; filozofia francuska